The effects of partitions on the vibration serviceability of concrete floors - Mutombo, Christian Kabongo (Department of Civil Engineering, 2016)
The growing demand to construct long, slender floors with minimum supports for aesthetic and economic reasons especially in modern building developments has resulted in increased floor slenderness leading to vibration problems. As a result, vibration serviceability has become the governing design criterion for many of these new civil engineering structures. It is known that long span, slender floors possess lower natural frequencies and reduced damping leading to vibration serviceability problems. As vibration serviceability becomes a major concern in the design of concrete floors, investigations of the beneficial effects of non-structural elements to the vibration serviceability of floors are becoming increasingly important. The vibration serviceability of long span, slender concrete floors may be improved through the installation of non-structural elements such as partition walls and raised access floors. Little research exists into the quantification of the effects of various types of partitions on the vibration serviceability of concrete floors that support them. There are no guidelines available to designers which take into account the effects of partitions in the design of concrete floors for vibration serviceability besides the different damping ratios that are recommended in different codes for bare floors as well as floors with half- or full-height partitions. Therefore a research project was initiated with the objectives of investigating the effects of non-structural partitions on the vibration serviceability of concrete floors as well as proposing guidelines on how to account for partitions in the design of concrete floors for vibration serviceability. The research project consisted of modal testing on a prestressed pre-tensioned concrete floor slab. The excitation of the floor was generated by an electrodynamic shaker and instrumented impulse hammer. The electrodynamic shaker excitation was used mainly to extract the natural frequencies and mode shapes of the test floor. The instrumented impulse hammer excitation was used mainly for damping studies. Force-balanced QA 700 accelerometers with a sensitivity of 8 V/g mounted to base plates were used to measure the responses of the test floor. The Data Physics Signal Calc Mobilyser was used to acquire the data from the accelerometers. A personal computer was used to store, analyse and present the data. The curve fitting method in Vibrant Technologies ME'Scope was used to estimate the natural frequencies and mode shapes of the test floor. Modal 1.20 by Brownjohn (2009) was used to estimate the damping ratios of the test floor. Modal 1.20 uses the logarithmic decrement method to estimate damping. The tests investigated the effects of partitions on the vibration serviceability of concrete floors.